MARKETING MANAGEMENT IN INCREASING THE QUANTITY OF NEW STUDENTS - Sarip Besan; Moch. Chotib; Lailatul Usriyah (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze the implementation of educational marketing management in increasing the quantity of new students at Pondok Pesantren Al-Ishlah Bondowoso. The study specifically examines planning, organizing, and controlling aspects of educational marketing management implemented by the pesantren management. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation techniques involving pesantren leaders, administrators, teachers, and parents of students. Data validity was examined through source triangulation and method triangulation. The findings reveal that marketing planning was conducted through annual coordination meetings involving all institutional stakeholders. Marketing organization was implemented by establishing a special committee responsible for promotion, publication, and student recruitment. Meanwhile, marketing control was carried out through periodic evaluations of promotional programs and annual student admission achievements. The implementation of educational marketing management succeeded in increasing the number of new students significantly every year. The success was supported by digital media utilization, alumni networking, institutional reputation, and the quality of educational services provided by the pesantren. Therefore, educational marketing management has become a strategic instrument in strengthening the competitiveness of Islamic boarding schools in the modern era.